Regulatory network controls microbial biofilm development, with Candida albicans as a representative: from adhesion to dispersal. Issue 1 (1st January 2022) - Xu, Zhenbo; Huang, Tengyi; Min, Du; Soteyome, Thanapop; Lan, Haifeng; Hong, Wei; Peng, Fang; Fu, Xin; Peng, Gongyong; Liu, Junyan; Kjellerup, Birthe V.
ABSTRACT: Microorganisms mainly exist in the form of biofilm in nature. Biofilm can contaminate food and drinking water system, as well as cause chronic wound infections, thereby posing a potential threat to public health safety. In the last two decades, researchers have made efforts to investigate the genetic contributors control different stages of biofilm development (adherence, initiation, maturation, and dispersal). As an opportunistic pathogen, C. albicans causes severe superficial or systemic infections with high morbidity and mortality under conditions of immune dysfunction. It has been reported that 80% of C. albicans infections are directly or indirectly associated with biofilm formation on host or abiotic surfaces including indwelling medical devices, resulting in high morbidity and mortality. Significantly, the outcome of C. albicans biofilm development includes enhanced invasion, exacerbated inflammatory responses and intrinsic resistance to antimicrobial chemotherapy. Thus, this review aimed at providing a comprehensive overview of the regulatory network controls microbial biofilm development, with C. albicans as a representative, served as reference for therapeutic targets.